Germinação, morfometria e qualidade ecológica em matrizes de dalbergia miscolobium benth - Bragiola, Natália Guariglia (2016)
The knowledge of fruits and seeds features plus the quality and strength of Dalbergia miscolobium are highly important to the reproduction of these species in restoration programs. Our study aimed to evaluate the viability, germination and morphometry of D. miscolobium seeds in order to select reproductive individuals bearing good silvicultural features, aiming to collect and propagate seeds. For this purpose, we collected fruits from 10 matrices in 2 distinct cerrado sensu stricto areas, measuring their length, width and thickness, analyzing the quality of seeds and classifying them according to their strength. We performed the 1% tetrazolium test, which allowed us to classify the seeds as viable or unviable ones. We put seeds from 5 collected matrices to germinate and in their germination on a daily basis. At the end of the experiment, we calculated the germination and mortality indexes plus the fresh and dry mass of seedlings. We found significant difference amongst the fruits and seeds from 10 matrices, which points that the viability of a species can be affected by climate and biotic factors, besides their own genetics. The length of fruits ranged from 40 to 49 mm, the width ranged from 16,6 to 20,3 mm while the length of seeds ranged from 14,8 to 17,2 and their width ranged from 6,9 to 8,0 mm. The seeds of D. miscolobium showed a good quality and we found them intact in the most of times, although we observed a higher predation rate in comparison to literature and we recorded a low abortion rate. We classifyed the fruits as anemochorous, dry and winged samara style. The tetrazolium test showed a high viability for D. miscolobium seeds pointing that the allotment of seeds bears good quality. We recorded a higher germinability and germination speed on matrices 4 and 5 poiting their ability to germinate in ideal conditions. On the other hand, the matrices 1, 2 and 3 showed a long germination time and a low germination speed, which leads to the conclusion that these seeds bear a lower germinability against the environment conditions in which they were planted, hampering the germination of seedlings from these matrices. The dry mass of roots was the only one that showed significant difference amongst the other measures, accumulating the largest part of biomass, which gives an advantage during the initial stage of seedlings establishment, since they can absorb water and nutrients on a larger contact surface. On the other hand we did not observe a remarkable growth of the aerial parts. According to our results, we can affirm that the matrices are highly variable in all the observed standards, pointing to genetic variability in this species thus, it is important to select good matrices in order to achieve positive responses in germination, producing good quality and strong seedlings proper for revegetation and restoration purposes.